Exploring EGPA: Clinical perspectives on peripheral eosinophilia and lung involvement with real-life data. - Ocal, Nesrin; Dogan, Deniz; Ocal, Ramazan; Arikan, Beste; Alsat Guray, Sebnem; Dincer, Aysuna; Agilli, Mehmet; Arslan, Yakup; Tasci, Canturk (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Introduction: The role of eosinophils in acute and chronic lung diseases becomes more evident day by day. The aim of this study is to analyze the guiding role of peripheral eosinophilia in the diagnosis of lung diseases and to present pulmonologists’ perspective on EGPA with old and new diagnostic criteria through real-life data. Patients and Methods: In this retrospective observational cohort, the files of patients who presented to the chest diseases department with pulmonary symptoms and peripheral eosinophilia between 2017-2023 were investigated. The diagnoses of the patients and their eosinophilia severity were examined. All the cases were reviewed according to the old and new diagnostic criteria for EGPA. Results: Among the 1567 patients with pulmonary symptoms and peripheral eosinophilia, pulmonary infection was the most common cause, followed by asthma and COPD. Mild eosinophilia was detected in the majority of the patients (90.5%). The highest mean eosinophil counts were observed in malignancies, hematological diseases and rheumatological diseases (including EGPA), respectively. Eosinophilia severities had significant difference between the diagnostic subgroups (p<0.001). The data were revised for EGPA with old and current diagnostic criteria. The false positivity rate of the old criteria was found to be significantly higher than the correctly applied current criteria (92.8% and 33.3%). Proper application of the current classification criteria regarding EGPA, which is among the causes of severe eosinophilia, will prevent unnecessary tests in this regard.